Interaction of the tachykinin NK3 receptor agonist senktide with behavioral effects of cocaine in marmosets (Callithrix penicillata). - de Souza Silva, MA; Mello, E; Müller, C; Jocham, G; Maior, R; Huston, J; Tomaz, C; Barros, M (2006)
Brain neuropeptide transmitters of the tachykinin family are involved in the organization of many behaviors. However, little is known about their contribution to the behavioral effects of drugs of abuse. Recently, antagonism of the tachykinin NK3-receptor (NK3-R), one of the three tachykinin receptors in the brain, was shown to attenuate the acute and chronic behavioral effects of cocaine in rats and the acute effects in non-human primates. In order to expand these findings we investigated the effects of the NK3-R agonist, succinyl-[Asp6, Me-Phe8]SP(6-11) (senktide), on the acute behavioral effects of cocaine in marmoset monkeys (Callithrix penicillata) using a figure-eight maze procedure. Animals were pretreated with senktide (0, 0.1, 0.2, 0.4 mg/kg, s.c.), and received either a treatment with cocaine (10 mg/kg) or saline (i.p.). Cocaine increased locomotor activity and the duration of aerial scanning behavior, but reduced exploratory activity, bodycare activity, the frequency of aerial scanning, and terrestrial glance behavior. Senktide blocked the effects of cocaine on locomotor activity, but enhanced the cocaine effects on exploratory activity, aerial scanning frequency, and terrestrial glance behavior. Senktide alone did not significantly influence monkey behavior in this study. These data expand previous findings suggesting a complex role of the NK3-R in the acute behavioral effects of cocaine in non-human primates.